The Determinants of Capital Structure for The Coal-Mining Companies Listed on Indonesia Stock Exchange - Venny Venny; Sarwo Edy Handoyo (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this research is to explain the effect of profitability, asset structure, growth opportunities, and non-debt tax shields on the capital structure of the coal-mining firms indexed on the Indonesia Stock Exchange from 2016 to 2020. There are 12 company samples in this research, which was determined with the purposive sampling method. The series of tests that will be carried out in this study include descriptive statistical analysis, panel data regression model tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The data are processed using the EViews 12 software. The outcomes of this study show that profitability (ROA) and non-debt tax shields (NDTS) are affecting the capital structure (DER) negatively and significantly, growth opportunities (MTB) is affecting the capital structure (DER) positively and significantly, while asset structure (TANG) does not affect the capital structure significantly.